Kesetaraan Gender dalam Perspektif Al-Qur’an dan Implikasinya terhadap Hukum Islam - Sarifa Suhra (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
In this paper, the writer emphasises justice and equality in the perspective of the Qur'an and the Hadith. Islam as a religion holds the values of justice and equality contains the principles of equality. Both men and women are equally as worshippers of Allah; men and women alike as the leaders on this earth; they alike receive primordial covenant. It is believed that Adam and Eve were both active in the cosmic drama, men and women have the potential to achieve optimal performance. The implementation of the gender equality based on the perspective of the Qur'an in Islamic law leads to the transformation of Islamic law relating to the issues of the relation of equality between men and women. It is also within professional fields such as the female judge whose produce the legal products based on gender equality .